Efektivitas Pelatihan Kecerdasan Adversitas Berbasis Islam Untuk Meningkatkan Daya Juang Mahasiswa Baru UIN Antasari Banjarmasin - Hidayat Ma'ruf (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
Students are vulnerable to experiencing many problems that negatively impact their quality of life. Due to this issue, it is needed the mental strength and high resilience to make their dreams come true. However, students who have strong religiosity, their perception and conception of life are strongly influenced by their religious belief systems. Training to change attitude and to develop motivation is therefore very important. This study attempted to look at the effectiveness of Islamic-based adversity intelligence training to improve new students’ resilience of State Islamic University (UIN) Antasari Banjarmasin. This study used the experimental method with a one-group pretest-posttest design. Data were analyzed with quantitative descriptive analysis (QDA). The effectiveness of training was measured by comparing the results of the resilience level scores before and after training (pretest-posttest) using the Wilcoxon test analysis through SPSS version 16.0. The results showed that Islamic-based adversity intelligence training is very effective to improve new students’ resilience.